Paleomagnetic evidence for late Cenozoic glaciations in the Mackenzie Mountains of the Northwest Territories, Canada - Barendregt, R. W.; Enkin, R. J.; Baker, J.; Duk-Rodkin, A. (Canadian Journal of Earth Sciences, 1996)
The Mackenzie Mountains were affected by montane valley glaciers during the Pleistocene and peripherally by the Laurentide Ice Sheet during the last glaciation. In this paper we report on magnetostratigraphic dating and correlation of three sections recording Late Pliocene to Late Pleistocene glaciations: Katherine Creek, Little Bear River, and Inlin Brook (located around 65°N, 127°W). Each section consists of a colluvial unit overlying a Pliocene pediment surface cut into Proterozoic or Paleozoic bedrock, or Tertiary gravel, which is in turn overlain by a stack of five, and in places six, montane tills, usually with soils developed at their surfaces, and capped by a Laurentide till. Normal and reversed magnetizations were recognized with single-domain magnetite as a dominant remanence carrier. The Katherine Creek section has a normally magnetized colluvium at its base, which is overlain by two reversed tills, succeeded by three normal tills. We interpret the top two tills to be of Brunhes age (< 780 ka) but argue that the lowermost normal till is of probable Olduvai age (ca. 1.8 Ma). The two underlying tills are of Matuyama age (2.6 Ma to 780 ka), and the colluvial base is assigned to the Gauss (3.5–2.6 Ma). The Little Bear River section exposes a stratigraphic record similar to that found at Katherine Creek. Only four units could be assigned a paleomagnetic polarity, the others yielding incoherent results. Paleosols on the first and second till units were reversed and normal, respectively, and the top till was normal. Thus there is clear evidence of an older (reversed) Pleistocene glaciation and a magnetostratigraphic record compatible with that found at Katherine Creek. Magnetic measurements from Inlin Brook gave largely incoherent results, with the exception of the surface (Laurentide) till, which is normal. The glacial history recorded in the Mackenzie Mountains correlates well with other studies carried out in the Cordillera. The large-scale changes in climate revealed in these terrestrial records ...